2013
DOI: 10.5617/jeb.443
|View full text |Cite
|
Sign up to set email alerts
|

Impedance of tissue-mimicking phantom material under compression

Abstract: The bioimpedance of tissues under compression is a field in need of study. While biological tissues can become compressed in a myriad of ways, very few experiments have been conducted to describe the relationship between the passive electrical properties of a material (impedance/admittance) and its underlying mechanical properties (stress and strain) during deformation. Of the investigations that have been conducted, the exodus of fluid from samples under compression has been thought to be the cause of changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
(46 reference statements)
3
16
0
Order By: Relevance
“…They suggest that the different resistivity of each type of tissue can be an indicator of its structure. Belmont's test [27] on a soft tissue-mimicking phantom showed a decrease in the admittance of the phantom under compression. They showed that tofu can be used as a suitable phantom for bioimpedance measurements under applied pressure.…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that the different resistivity of each type of tissue can be an indicator of its structure. Belmont's test [27] on a soft tissue-mimicking phantom showed a decrease in the admittance of the phantom under compression. They showed that tofu can be used as a suitable phantom for bioimpedance measurements under applied pressure.…”
Section: Introductionmentioning
confidence: 99%
“…3) was based on the tetrapolar BIS circuit designed and developed by Dodde et al [25,27,28,29]. Our system consisted of a BIS circuit, four platinum leaf probes, an oscilloscope (DSO7032B, Agilent Technologies, Santa Clara, CA), a single-axis programmable mechanical test stand (ESM301L, Mark-10, Copiague, NY), and a computer for automation and data acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…Ohm's law was then used to calculate the impedance. Tetrapolar probes have been previously used in a number of BIS studies and are widely considered to be reliable [27,31]. The schematic for the circuit used in our compression BIS system is shown in Fig.…”
Section: Design and Characterization Of The Bis Circuitmentioning
confidence: 99%
See 2 more Smart Citations